2010
DOI: 10.1177/104063871002200205
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Urinary F2-Isoprostanes as Markers of in Vivo Lipid Peroxidation: A Comparison of Enzyme Immunoassays with Gas Chromatography–Mass Spectrometry in Domestic Animal Species

Abstract: F(2)-isoprostanes are useful markers for assessing oxidant injury; however, the validity of measuring urinary 15-F(2t)-isoprostane concentration by enzyme-linked immunosorbent assay (ELISA) has not been evaluated in veterinary species. The current study assesses the agreement between 2 commercially available urinary isoprostane kits and gas chromatography and negative ion chemical ionization-mass spectrometry (GC/NICI-MS). The results indicate that only feline urinary isoprostane measurement by glucuronidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 52 publications
1
41
2
Order By: Relevance
“…We used an immunoassay for IsoP measurements, rather than 1 of several mass spectrometry (MS) methods that are considered gold standards,41 but MS methods are more expensive and labor‐intensive,41 and suboptimal for veterinary use. In a previous study in 20 cats, the same Cayman ELISA (with slightly different preparative steps) correlated significantly with gas chromatography/negative ion chemical ionization‐MS, but the correlation was somewhat weak ( r = 0.678), with the ELISA measuring lower concentrations than MS (fixed bias), and sometimes missing low concentrations that were detectable by MS (proportional bias) 42. In our study, we did not have the same sensitivity problem and were able to detect urinary IsoPs in all cats.…”
Section: Discussionmentioning
confidence: 87%
“…We used an immunoassay for IsoP measurements, rather than 1 of several mass spectrometry (MS) methods that are considered gold standards,41 but MS methods are more expensive and labor‐intensive,41 and suboptimal for veterinary use. In a previous study in 20 cats, the same Cayman ELISA (with slightly different preparative steps) correlated significantly with gas chromatography/negative ion chemical ionization‐MS, but the correlation was somewhat weak ( r = 0.678), with the ELISA measuring lower concentrations than MS (fixed bias), and sometimes missing low concentrations that were detectable by MS (proportional bias) 42. In our study, we did not have the same sensitivity problem and were able to detect urinary IsoPs in all cats.…”
Section: Discussionmentioning
confidence: 87%
“…Second, they provide a noninvasive route for systemic oxidative stress evaluation. Although they can also be locally produced in the kidney, many studies have demonstrated that urinary F2-isoprostanes are mainly derived from free F2-isoprostanes filtered from the circulation [97,149,151,152]. Only hydrolyzed isoprostanes are excreted into the urine whereas blood plasma samples contain both free and esterified isoprostanes.…”
Section: F2-isoprostanesmentioning
confidence: 99%
“…Furthermore, F2-isoprostanes have been shown to exert potent vasoconstrictor effects on animal and human vessels, suggesting a pathogenic role in cardiovascular diseases and have been extensively used as markers of lipid peroxidation in human diseases [74,75,148]. Their high stability and presence in measurable concentrations in many biological tissues and fluids, under physiological and pathological conditions, has also allowed the establishment of reference intervals and the comparison or monitoring of disease states [97,149,150]. Urine specimens are particularly suited for F2-isoprostanes measurements.…”
Section: F2-isoprostanesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the monitoring of lipid peroxidation, spectrophotometric [30,31], chromatographic [32] and immunochemical [33] methods can be used. The analysis itself may be based on the analysis of the primary products of lipid peroxidation as conjugated dienes [34] and lipid hydroperoxides [35], or secondary products, such as malondialdehyde [36], alkanes [37] or isoprostanes [32,[38][39][40]. Chromatographic methods represent the special group of methods, which are mostly based on the decrease of unsaturated fatty acids' concentration [41].…”
Section: Introductionmentioning
confidence: 99%